A phase I study of an agonist CD40 monoclonal antibody (CP-870,893) in combination with gemcitabine in patients with advanced pancreatic ductal adenocarcinoma - Beatty, Gregory L. (2013)
PURPOSE: This phase I study investigated the maximum-tolerated dose (MTD), safety, pharmacodynamics, immunological correlatives, and anti-tumor activity of CP-870,893, an agonist CD40 antibody, when administered in combination with gemcitabine in patients with advanced pancreatic ductal adenocarcinoma (PDA). EXPERIMENTAL DESIGN: Twenty-two patients with chemotherapy-naïve advanced PDA were treated with 1000 mg/m(2) gemcitabine once weekly for 3 weeks with infusion of CP-870,893 at 0.1 mg/kg or 0.2 mg/kg on day 3 of each 28 day cycle. RESULTS: CP-870,893 was well-tolerated; one dose-limiting toxicity (grade 4 cerebrovascular accident) occurred at the 0.2 mg/kg dose level, which was estimated as MTD. The most common adverse event was cytokine release syndrome (grade 1 to 2). CP-870,893 infusion triggered immune activation marked by an increase in inflammatory cytokines, an increase in B cell expression of co-stimulatory molecules, and a transient depletion of B cells. Four patients achieved a partial response (PR). [(18)F]-fluorodeoxyglucose-positron emission tomography/computed tomography (FDG-PET/CT) demonstrated >25% decrease in FDG uptake within primary pancreatic lesions in 6 of 8 patients; however, responses observed in metastatic lesions were heterogeneous with some lesions responding with complete loss of FDG uptake while other lesions in the same patient failed to respond. Improved overall survival correlated with a decrease in FDG uptake in hepatic lesions (R = −0.929; p = 0.007). CONCLUSIONS: CP-870,893 in combination with gemcitabine was well-tolerated and associated with anti-tumor activity in patients with PDA. Changes in FDG uptake detected on PET/CT imaging provide insight into therapeutic benefit. Phase II studies are warranted.